The Intrinsic Flattening of Galaxy Disks - Jeremy Favaro; Stéphane Courteau; Sébastien Comerón; Connor Stone (The Astrophysical Journal)
Highly inclined (edge-on) disk galaxies offer the unique perspective to constrain their intrinsic flattening, c / a , where c and a are, respectively, the vertical and long radial axes of the disk measured at suitable stellar densities. The ratio c / a is a necessary quantity in the assessment of galaxy inclinations, three-dimensional structural reconstructions, and total masses, as well as a constraint to galaxy formation models. The 3.6 μ m maps of 133 edge-on spiral galaxies from the Spitzer Survey of Stellar Structure in Galaxies (S ^4 G) and its early-type galaxy extension are used to revisit the assessment of c / a free from dust extinction and away from the influence of a stellar bulge. We present a simple definition of c / a and explore trends with other galactic physical parameters: total stellar mass, concentration index, total H i mass, mass of the central mass concentration, circular velocity, model-dependent scales, and Hubble type. Other than a dependence on early/late Hubble types and a related trend with light concentration, no other parameters were found to correlate with the intrinsic flattening of spiral galaxies. The latter is mostly constant with 〈 c / a 〉 = 0.124 ± 0.001 (stat) ± 0.033 (intrinsic/systematic) and greater for earlier types.